Loss of SMARCA4 (BRG1) protein expression as determined by immunohistochemistry in small‐cell carcinoma of the ovary, hypercalcaemic type distinguishes these tumours from their mimics. Issue 5 (28th July 2016) - Clarke, Blaise A; Witkowski, Leora; Ton Nu, Tuyet N; Shaw, Patricia A; Gilks, C Blake; Huntsman, David; Karnezis, Anthony N; Sebire, Neil; Lamovec, Janez; Roth, Lawrence M; Stewart, Colin J R; Hasselblatt, Martin; et al.
Abstract : Aims: Molecular investigation of small‐cell carcinoma of the ovary, hypercalcaemic type (SCCOHT) has revealed that it is a monogenetic tumour characterized by alteration of SMARCA4 ( BRG1 ), encoding a member of the switch/sucrose non‐fermentable (SWI/SNF) chromatin remodelling complex. A large majority of cases show loss of expression of the corresponding SMARCA4/BRG1 protein. Furthermore, three cases of SCCOHT with retained SMARCA4 protein expression showed loss of SMARCB1/INI1 expression. The aim of this study was to assess the sensitivity and specificity of loss of SMARCA4 expression as a diagnostic test for SCCOHT. Methods and results: We performed SMARCA4 and SMARCB1 staining in 245 tumours, many of which were potentially in the differential diagnosis of SCCOHT. We also stained 56 cases of SCCOHT for SMARCA4 and 37 of these for SMARCB1. Fifty‐four of the SCCOHT cases showed complete absence of SMARCA4 expression. The two cases with retained expression showed molecular alteration of SMARCA4 . Of the 217 other neoplasms with interpretable staining, all retained SMARCA4 expression. Although the majority showed diffuse, strong nuclear expression, a heterogeneous, typically weak staining pattern was present in 13% of cases. All 37 cases of SCCOHT tested and all other neoplasms, apart from three malignant rhabdoid tumours, showed retained nuclear SMARCB1 expression. Loss of SMARCA4 expression had a sensitivity of 96.55% and specificity of 100%. Conclusions: Loss of SMARCA4 expression is sensitive and specific for SCCOHT. Although some mimics show heterogeneous expression, there is retention of nuclear staining in at least a part of the tumour; therefore, only complete loss of staining should be regarded as being supportive of SCCOHT.